Nanoparticle albumin-bound paclitaxel – first step of nanotechnology into clinical practice - R. N. Alyautdin; B. K. Romanov; В. К. Лепахин; N. D. Bunyatyan; V. A. Merkulov; A. N. Mironov (Безопасность и риск фармакотерапии, 2022)
Paclitaxel is an effective antitumor agent used for treatment of breast cancer, lung, stomach and pancreas. However, its own adverse effects and the use of toxic Cremophor EL as the solvent limit the application range of this drug. Associated with the albumin-bound nanoparticle paclitaxel (paclitaxel SAN) specifically transported into tumor tissue. This leads to an increase in the antitumor effect, and it reduces the severity of side effects.